Analytical formulation of relationship between ionization current and extracted ion beam current in a Penning ion source - Silakhuddin, Silakhuddin; Kudus, Idrus Abdul; Jati, Bambang Murdaka Eka; Palupi, Dwi Satya; Taufik, Taufik; Mulyani, Emy; Heranudin, Heranudin (Institute of Advanced Engineering and Science, 2026)
A study on the performance of the Penning-type internal ion source of the DECY-13 cyclotron has been conducted to evaluate the relationship between cathode current and extracted ion beam current, as well as the stability of the extracted beam. The DECY-13 cyclotron, developed at the Research Center of Accelerator Technology, BRIN, is designed to produce 13 MeV protons for radioisotope production. In the experiment, the cathode current was varied between 200-400 mA, while the magnetic field and extraction voltage at 1.25 T and 3 kV, respectively. The results indicate a clear power-law dependence between cathode current (Ic) and extracted beam current (Iext), expressed as Iext=343.8 Ic^1.42 . This relationship suggests that ionization efficiency increases sharply with cathode current. Stability tests at 400 mA cathode current showed that the extracted beam current remained stable at 70 μA over 45 minutes, with only minor fluctuations. These findings demonstrate that cathode current is an effective parameter for controlling extracted beam current. The results contribute to a better understanding of ion source behavior in cyclotron systems and provide a foundation for further optimization of Penning ion sources for radioisotope production.